2024
DOI: 10.1126/sciadv.adk6285
|View full text |Cite
|
Sign up to set email alerts
|

Thinner is not always better: Optimizing cryo-lamellae for subtomogram averaging

Maarten W. Tuijtel,
Sergio Cruz-León,
Jan Philipp Kreysing
et al.

Abstract: Cryo–electron tomography (cryo-ET) is a powerful method to elucidate subcellular architecture and to structurally analyze biomolecules in situ by subtomogram averaging, yet data quality critically depends on specimen thickness. Cells that are too thick for transmission imaging can be thinned into lamellae by cryo–focused ion beam (cryo-FIB) milling. Despite being a crucial parameter directly affecting attainable resolution, optimal lamella thickness has not been systematically investigated nor the extent of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…4d,e). The limit of the depth of damage is comparable to other studies using argon (Berger et al, 2023; Chaillet et al, 2023; Parkhurst et al, 2023) and gallium beams (Lucas and Grigorieff, 2023; Yang et al, 2023; Tuijtel et al, 2024), despite notable differences in methodology, each of which have relative merits. Regardless of the technique used, it is important to correct for variations in factors such as local lamella thickness, motion and charging.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…4d,e). The limit of the depth of damage is comparable to other studies using argon (Berger et al, 2023; Chaillet et al, 2023; Parkhurst et al, 2023) and gallium beams (Lucas and Grigorieff, 2023; Yang et al, 2023; Tuijtel et al, 2024), despite notable differences in methodology, each of which have relative merits. Regardless of the technique used, it is important to correct for variations in factors such as local lamella thickness, motion and charging.…”
Section: Discussionsupporting
confidence: 73%
“…Using in situ subtomogram averaging and B-factor analysis (Rosenthal and Henderson, 2003), it was demonstrated that 30 kV argon PFIB milling on biological samples results in damage characterised by reduced information content at depths up to 30 to 45 nm from the milling surfaces (Berger et al, 2023). The damage layer for 8 kV and 30 kV gallium FIB milling has been characterised (Lucas and Grigorieff, 2023;Yang et al, 2023;Tuijtel et al, 2024), reporting penetration depths for the damage between 30 and 60 nm, with reduced depth of damage at lower voltage FIB milling. We present a workflow for the use of xenon PFIB milling to prepare lamellae from ~25 µm thick highpressure frozen biological samples with currents up to 60 nA.…”
Section: Introductionmentioning
confidence: 99%